Analisis Peran Artificial Intelligence Dalam Mendeteksi Pola Transaksi Mencurigakan Sebagai Upaya Pencegahan Pencucian Uang - Najma Azzahra Annisa Suri; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Advances in information technology have brought significant changes to efforts to prevent and combat money laundering. One innovation that plays an important role in detecting suspicious transactions is Artificial Intelligence (AI). This study aims to analyse the role of AI in identifying transaction patterns that may constitute money laundering crimes, with a focus on AI's ability to process data quickly and accurately. The method used in this study is a qualitative study with a descriptive-analytical approach. The results of the study indicate that the application of AI in financial systems, particularly through machine learning and data mining techniques, can significantly improve the effectiveness of early detection of suspicious transactions. However, challenges such as algorithmic bias, limitations of historical data, and regulatory aspects pose obstacles that need to be addressed. This study suggests collaboration between financial authorities, technology institutions, and regulators to optimise the use of AI within a suitable legal framework.